Checklist of Birds of the Everglades Agricultural Area - Elise V. Pearlstine; Frank J. Mazzotti (EDIS, 2011)
This revised 9-page fact sheet features a checklist of bird species that have been found during eight years of surveys in the Everglades Agricultural Area. Most birds can be associated with a specific habitat such as sugarcane, sod, rice or flooded fields and other agricultural and human-inhabited areas. Written by Elise V. Pearlstine and Frank J. Mazzotti and published by the UF Department of Wildlife Ecology and Conservation, November 2010. Reviewed December 2013.